Pengaruh Electronic Word Of Mouth (E-Wom) dan Brand Trust Terhadap Purchase Decision Produk Wardahdi Kota Pekanbaru - Salwa Julianti; Syofiatul Safitri (LPPM Universitas Sains dan Teknologi Komputer, 2026)
This research focuses on analyzing the role of electronic word of mouth (e-WOM) communication and brand trust in influencing purchase decisions for Wardah products in Pekanbaru. This study employs quantitative methods using two data sources: primary and secondary data. Primary data were collected through questionnaires distributed to 96 female Wardah users aged 17 to 35 years residing in Pekanbaru. Respondents were selected using purposive sampling based on specific criteria established by the researcher. All variable indicators were measured using a Likert scale to obtain quantitative assessments from respondents. Data processing and analysis were carried out through a series of statistical steps, including instrument testing (validity and reliability), classical assumption testing, multiple linear regression analysis, partial and simultaneous hypothesis testing (t-test and F-test), and calculating the coefficient of determination (R²) using SPSS software. The test results indicate that e-WOM communication significantly increases consumers' likelihood of making purchase decisions. Likewise, brand trust has been shown to contribute positively and significantly to these decisions. Together, these two independent variables significantly explain variations in Wardah product purchasing decisions in Pekanbaru. This confirms that the quality of digital information consumers receive and confidence in brand credibility are important factors in driving purchases